Amitav Ghosh, a critical companion - Tabish Khair (ed.) (Delhi : Permanent Black : Distributed by Orient Longman, 2003)
Contributed articles on the life and works of Amitav Ghosh, Indian English author.
Keywords: Novel English Criticism; Literature English; Literature